2010
DOI: 10.1002/nme.2899
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive mesh refinement applied to the scalar transported PDF equation in a turbulent jet

Abstract: SUMMARYThis paper describes a novel solution method for the transported probability density function (PDF) equation for scalars (compositions). In contrast to conventional solution methods based on the Monte Carlo approach, we use a finite-volume method combined with adaptive mesh refinement (AMR) applied in both physical and compositional space. The obvious advantage of this over a uniform grid is that fine meshes are only used where the solution requires high resolution. The efficiency of the method is demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…It can be seen that the effect of the intermittency is not only responsible for improved predictions on the jet centreline, but also for the bimodal distributions associated with its increasing influence with radial distance. Apart from on the centre-line, the implementation of  in the LMSE molecular mixing model, as seen in Equation (8), is the primary influence in this respect, with the effect of  in the flow Equations (11) and (13) a secondary effect. All the present results given in Figure 6 are also superior to those obtained in earlier work [15] which used the three-part, prescribed PDF approach of Effelsberg and Peters [27] and which failed to predict the bimodal distributions observed experimentally.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It can be seen that the effect of the intermittency is not only responsible for improved predictions on the jet centreline, but also for the bimodal distributions associated with its increasing influence with radial distance. Apart from on the centre-line, the implementation of  in the LMSE molecular mixing model, as seen in Equation (8), is the primary influence in this respect, with the effect of  in the flow Equations (11) and (13) a secondary effect. All the present results given in Figure 6 are also superior to those obtained in earlier work [15] which used the three-part, prescribed PDF approach of Effelsberg and Peters [27] and which failed to predict the bimodal distributions observed experimentally.…”
Section: Resultsmentioning
confidence: 99%
“…This contrasts with more conventional approaches which are based on the use of finitevolume methods in physical space, and Monte Carlo methods in compositional space for solution of the PDF equation. This work [7,8] also demonstrated that, for small numbers of scalar variables, AMR provides improved accuracy, run times and ease of use over alternative Monte Carlo approaches. AMR is now a well-established technique, having its earliest applications in two-dimensional shock problems [9,10], with subsequent extension to three-dimensional flows [11] and implementation on parallel computers [12].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…For PDF transport modeling, there has been little investigation of techniques to reduce the runtime for the solution of the PDF transport model. The exception to this is the work of Fairweather et al [17][18][19], where an adaptive finite volume mesh algorithm is used to solve the PDF transport model for some idealized nonreacting and reacting flows. This is computationally frugal for many situations, where only a small region of parameter space requires a fine grid to resolve the PDF and is a technique that has been applied successfully to shock capturing in compressible flows [20] and radiation heat flux calculation in fire modeling [21].…”
Section: Introductionmentioning
confidence: 96%